Preparation of ceftiofur nanoemulsion and its antimicrobial effect on major pathogenic bacteria of bovine mastitis - LIANG Siyuan; WANG Yuemin; HU Songhua (浙江大学学报. 农业与生命科学版)
Ceftiofur nanoemulsion (CNE) with stable property was made of Tween-80, glycerine, soybean oil, water, ceftiofur and dimethyl sulfoxide (DMSO), which was detected as an oil-in-water nanoemulsion with an average diameter of 60.54 nm. To investigate the distribution of CNE in milk, ceftiofur sodium (CS) and CNE were incubated for 12 h at 37℃ in milk containing Staphylococcus aureus or Escherichia coli, and then the colony was counted in upper, middle and lower parts of milk. The results showed that from upper part to lower part, the colony counts were increased successively in the CNE-treated milk, which was on the contrary in the CS-treated milk, indicating that CNE tended to distribute in the upper part, while CS tended to distribute in the lower part. To further explore the therapeutic effect of CNE on bacterial infection, mice infected S. aureus were injected with CS or CNE at a dose of 19.1, 38.2 and 57.3 μmol/kg, respectively. In the CS-treated group, the survival rates of mice were 40%, 50% and 70%, respectively; while in the CNE-treated group, the survival rates of mice were 40%, 70%and 80%, respectively. Therefore, CNE had superior therapeutic effect. This study provides reference values for clinical use of CNE to treat bacterial infection.